ESTETIKA DALAM SENI ISLAM MENURUT SAYYED HOSSEIN NASR - ., Iswahyudi (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
The discussion about the phenomenon of religion and the cultural arts system is very interestingbecause the two have a close relationship. Islamic art, according to Nasr, has three elements.First, religious art is art that completely avoids something secular, can be a fence of expressionto hold back pagan art or the like. Secondly, Islamic art must be extracted from aesthetic elementswhich must animate the meaning of monotheism, so that it contributes to always remind againof the majesty of God. Third, Islamic art must be truly wisdom, because it is inspired by spiritualvalues. Associated with aesthetics, is to provide beauty that reflects aspects of positive judgment.The problems that arise in this case, how far beauty can be felt by someone and once able toevaluate it. Ethical and aesthetic freedom are often seen in relation to diametric patterns. Binaryopposition between ethical freedom governed by various normative rules and aesthetic freedomthat tends to be explosive is often a problem especially when art is associated with religiousvalues. Based on this, it is known that Nasr paid great attention to spirituality in building hisphilosophy of Islamic aesthetics and rejecting modernism.